Calling for a united action to defeat COVID-19. Issue 3 (6th August 2020) - Overby, Madison; Pu, Qinqin; Wei, Xiawei; Wu, Min
Abstract: The widespread and lingering pandemic of COVID-19 is partly due to disjointed international countermeasures and policies enforced by different countries. We have been witnessing disparity in policies and measures in different countries and regions: some are in much better control than others. To effectively deal with this and future devastating pandemics, we as human beings must work together to coordinate a concerted, cooperative international policy to reduce or possibly avoid unnecessary health crises, and life and economic losses.